Microstructure and Adhesion Properties Post-Annealed Metallic Coating of Fecrbmnsi on Tube and Internal Structure Coal-Fired Boiler - Agung Purniawan; Hengki Irawan; Sigit Tri Wicaksono (Institut Teknologi Sepuluh Nopember, 2017)
Iron-chrome based metallic coating is generally used to increase the life-time tube and internal structure of coal-fired boiler. The most common method used is thermal spray coating. The advantages of this method are simple in application, repair, and low cost. The post-heat treatment coating on metallic coating applied by the thermal spray method can affect to adhesion properties, the number of porosity and microstructure of coating material. The objective of this study is to analyze the influence of post-annealing on the metallic coating FeCrBMnSi applied by Twin Wire Arc-Spraying (TWAS) method on microstructure and adhesion properties which is applied on tube and internal structure of coal-fired boiler. Post-annealing was performed after coating application in vacuum furnace with variety of temperature at 500oC, 600oC and 700o and holding time about 3 hours. Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS) were used to analyze the morphology of microstructure, the uniformity of the deposit layer, and the percentage of porosity. X- Ray Diffraction (XRD) was used to determine phase formation and composition phase. Then, Pull Off Test was performed for adhesion test that is referred to ASTM D4541. The results shows that increasing post-annealed temperature cause microstructure of coating more crystalline, percentage of porosity decreased from 3% As-sprayed to 1,4% at 700oC post-annealing temperature and it has an effect on the adhesion properties of coating which increase up to 25%.